The Digital Divide: An Inquiry from Feminist Perspectives - Gurung, Lina (Dhaulagiri Journal of Sociology and Anthropology, 2018)
Exponential use of ICT has brought colossal opportunities as well as challenges to the present society. In spite of increasing women’s involvement in Information, Communication and Technology (ICT) , gender inequality has yet remained critical across the nations and globe. The uneven access and skills to technology has intensified the degree of digital divide specially for the women. Further the multifaced attribute of ICT and its relation with women is changing discourses among the feminist scholars. This is a conceptual paper which focuses on the deliberations of different feminists based on optimistic and pessimistic perspectives. Some studies show that the gender digital divide is getting intense while some have reported of alleviating gaps with more involvement of women. The concept of digital divide is beyond the access and includes various dimensions such as perception, usage, motivation, participation and skills. The paper deals with the tension between utopian and dystopian views on technology benefits. Through literature review this conceptual paper examines and discusses the diverse standpoints of feminist scholars from west and east which buzzes to redefine the relationship of gender with technology. It recommends that empowerment of women in technological domain is equally important as social, economic and political. Further women should be motivated from within to embrace ICT and get benefitted from its prospects. Resisting modern technology in the digital era would further widen the digital gap and thus make difficult to observe gender equality. More studies are required to explore the strategies for technological empowerment of women.